Asking for Feedback: Helping Learners Get the Feedback They Deserve - Allison Mariani; Sarah-Anne Schumann; Helen Barrett Fromme; Matthew Zegarek; Sean Swearingen; Michael Ryan; Shalini Reddy (Association of American Medical Colleges, 2015)
Abstract Introduction Many workshops have been developed to train faculty and other educators in how to give feedback effectively. However, few focus on how to solicit feedback from the learner perspective. Thus, many learners continue to report not getting adequate feedback in both quality and quantity. Additionally, feedback is viewed as a dynamic and collaborative process between learners and educators, yet the role of the learner is rarely discussed. To address this issue, this curriculum was developed to train learners in these skills. Methods This workshop introduces students to the definition and principles of feedback, trains students to self-assess their clinical learning strengths and needs, and provides students with a framework for effectively asking for clinical feedback. It is modeled after Kolb's experiential learning cycle: Participants have a concrete experience with the first trigger tape, then reflect on that tape and their own experiences through discussion. They are next introduced to new frameworks on how to ask for feedback through a short didactic and finally experiment with their new knowledge through trigger tape analysis and discussion. Results In 2013, the workshop was delivered to third-year medical students and interns (internal medicine, pediatrics, family medicine) at three institutions. We were able to obtain pre/post knowledge and attitude surveys of the learners at each workshop. The data suggest a trend (not significant) towards higher knowledge of feedback solicitation and utilization skills, as well as appreciation for the importance of using these skills. Additionally, we used historical control data to compare the frequency of asking for feedback and the ability to utilize it. Interns did not show any significant differences, but medical students were significantly more likely to ask for feedback as the year progressed once they had taken the workshop. Discussion After residency program and medical school learner feedback, we were invited to return for the second year to deliver the curriculum again, and at one site, the curriculum is now an annual and expected part of the pediatric intern year and the third-year medical school curriculum. We have also started considering the delivery of this curriculum to faculty through faculty development programs. To do this, we would require new video scenarios specific to faculty.